Sistem Pengelolaan Inventory Gudang (Studi Kasus: PT. Papua Utama Mitra) - Bagus Aryo Herlambang; Edy Santoso; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Warehousing basically functions to store goods for production in large quantities and a certain time span which is then distributed to the intended location. Warehousing will be able to operate more easily if there is a Warehouse Management System. Warehouse Management System that uses information systems will be able to assist in the management and supervision of incoming goods and outgoing goods in the warehouse. At this time, there are still some warehousing companies that use manual system processes starting from inbound customer documents, and others. There are problems found in the Admin and Checker PT. Papua Utama Partners. On the admin side, the problem is in the form of Time Working Efficiency. In this case, Time Working Efficiency is very influential on the quality of the company because it will be able to slow down the time in processing the queue of incoming or outgoing goods. The main purpose of this research is to make it easier for the Admin to process incoming mail and allocate goods by developing a warehouse inventory management system. This study uses one of the development methods, namely the waterfall model. Based on the needs elicitation carried out, there are 24 functional requirements and 1 non-functional requirement. In unit testing, validation testing, and integration, each result is 100% valid.